The Digitalization of Shame (Al-Hayā’): Discourse Analysis and Reception of the ‘Velocity’ Meme in Islamic Preaching on Tiktok - Dafina Ainani Zahra; Dzatan Nitoqoin; Khoirun Niam; Iksan Kamil Sahri (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2026)
This study aims to analyze the phenomenon of “shame” from an Islamic perspective and its representation through “Meme Velocity” on the social media platform TikTok. Using a qualitative approach and content analysis, this study examines the narratives, diction, religious ideological affiliations, and audience responses to shame-themed memes disseminated by Salafi-aligned accounts. The novelty of this study lies in the concept of shame in Islam and the analysis of audience responses on social media. The findings reveal that shame in Islam is a noble virtue rooted in faith (al-Haya’) and serves as a means of self-restraint against forbidden acts. The analyzed memes promote the value of shame and critique current trends, particularly the “Velocity” trend, which is deemed contrary to Islamic values. This study also reveals that these memes trigger a variety of responses, ranging from support and prayers to hostile reactions, reflecting the dynamics of digital da’wah and audience reception. The contribution of this research lies in enriching the study of digital da’wah and how the concept of modesty in Islam is constructed through social media, as well as providing implications for digital da’wah practitioners and helping to understand the complexities of religious communication in the digital age.